EFFECT OF METHYL METHANE SULFONATE ON EHRLICH ASCITES CARCINOMA CELLS: DOSE EFFECT RELATIONSHIPS : Life Science-cytology - MAHADIMANE, P. VISHWAPRAKASH; V. VASUDEV (International Journal of Life Science and Pharma Research, 2013)
A well known monofunctional alkylating agent, Methyl methanesulfonate (MMS) has been employed to understand its influence on the chromosomes of Ehrlich ascites carcinoma (EAC) cells. The literature review revealed that there are no reports on this aspect. Hence, a dose range of 25 to 150mg/kg bw MMS were used and ascitic fluid was drawn from treated animals to analyze the chromosomal aberrations. The analysis of chromosomal aberrations revealed that there is significant increase in frequency of aberrations compared to controls. Further there was also a linear increase of aberrations as dose increased indicating the dose effect relationship. The results are discussed to highlight the exploitation of EAC model for clastogenicity in general and carcinogenesis in particular.